2019
DOI: 10.1038/sj.bdj.2019.49
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in the use of cone beam computed tomography: a survey of UK dental practices

Abstract: Cone beam computed tomography (CBCT) is increasingly seen in UK dental practices, but there is no published information regarding how it is used. The aim of the study was to obtain such information using a survey. Materials and Methods:A survey on aspects of justification, optimisation and training was distributed to all dental practices having CBCT equipment and a contract with Dental X-ray Protection Services (DXPS). Results:Seventy-one completed surveys were received (49% response rate). A wide range of CBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Sir, we read with interest your recent publication on the current practice in the use of cone beam CT in UK dental practices. 1 Although it is difficult to generalise based on the limited sample of respondents in this study, we share the concerns of the authors regarding the interpretation and reporting of CBCT scans. We would like to share our experience of referrals and associated imaging received in secondary care.…”
Section: Governance Concerns In Cbct Interpretation and Reportingmentioning
confidence: 69%
See 1 more Smart Citation
“…Sir, we read with interest your recent publication on the current practice in the use of cone beam CT in UK dental practices. 1 Although it is difficult to generalise based on the limited sample of respondents in this study, we share the concerns of the authors regarding the interpretation and reporting of CBCT scans. We would like to share our experience of referrals and associated imaging received in secondary care.…”
Section: Governance Concerns In Cbct Interpretation and Reportingmentioning
confidence: 69%
“…Once the root of the tooth is deemed to be involved with the inferior alveolar nerve (IAN) canal radiographically, there is a 20% risk of the patient developing temporary IANI and a 1-4% risk of developing permanent IANI with surgical removal. 1 With the push by managing bodies to find cost effective alternatives to providing high quality care, there have been oral surgery contracts commissioned to provide services in primary care settings, which are usually delivered by secondary care providers, through specialist dentists or dentists with specialist interests.…”
mentioning
confidence: 99%
“…Another concern is that hybrid panoramic/CBCT scanners have become more prevalent. 15 Hybrid CBCT scanners are relatively low-cost compared with dedicated CBCT scanners, and even comparable to the price of digital panoramic scanners. Hybrid CBCT scanners allow dentists to take in-clinic CBCT images directly instead of through external referrals, and to have the chance to make additional income.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cone beam computed tomography (CBCT) has become an effective diagnostic tool for evaluating dentition. [35][36][37] Some previous studies have demonstrated the advantages of CBCT in estimating dental age based on metric measurements in adults and children. [38][39][40][41] Some recent studies have investigated the use of CBCT to estimate the age of children and adults.…”
mentioning
confidence: 99%
“…However, OPTs have disadvantages, such as distortion, magnification, and lack of cross-sectional data, and are limited in ensuring the accuracy of a 3-dimensional (3D) object. In recent years, cone beam computed tomography (CBCT) has become an effective diagnostic tool for evaluating dentition 35–37 . Some previous studies have demonstrated the advantages of CBCT in estimating dental age based on metric measurements in adults and children 38–41 .…”
mentioning
confidence: 99%